PORTFOLIO OPTIMIZATION USING MEAN VARIANCE AND MEAN ABSOLUTE DEVIATION (MAD) RISK MEASURES WITH SPIRAL OPTIMIZATION METHODE - DINI (NIM : 20115030), FITRIA
This thesis discusses portfolio optimization using two risk measures, mean-variance model (Markowitz model) and mean absolute deviation model (Konno - Yamazaki model). The constraints of portofolio optimization in this thesis (1) buy-in threshold, a constraint to limit the proportion of each stock, (2) Cardinality is a constraint to limit the number of stock to be selected to build the portofolio, and (3) roundlot, constraint which required investors to transaction in lots. For the first step, it will solved single objective portofolio optimization that is to minimize risk and maximize return. After that, we will solve multi objective problem which both problems are involved. This portofolio optimization issue will be solved using the Spiral Dynamics method developed by Tamura and Yasuda in 2011.